The environmental degradation caused by the inadequate dispose of plastic packs: a case study - Silva, Claudionor Oliveira; Santos, Gilbertânia Mendonça; Silva, Lucicleide Neves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
Modern society is accustomed to living with the ease and versatility that high consumption forms offer. Given a high level of consumption, globalization, technological innovations that seek every day to ensure your space in the market, and thereby contribute to the socioeconomic balance. The modernization making life easier for the general public and the other side may generate environmental disorders is the case of plastic packaging has on the environment long term. With their disuse and dispose inappropriately environments, making them increasingly vulnerable human actions that occur due to cultural and behavioral habits of a large portion of the population that needs to reeducate themselves regarding the preservation and conservation of the environment. This research aims to inform and sensitize students and the school community about the environmental impacts caused by the improper disposal of plastic packaging in order to reduce their consumption and proper disposal in the environment by changing attitudes and behavior. Initially a literature review was done on solid waste, forms of waste disposal, waste sorting and plastic packaging. Later, it was used to apply a self lifting students’ prior knowledge articulated with the theoretical. As a result there was a recycling workshop and implementation of selective collection, accompanied by segments of the school and municipal representatives. The results show that many students did not know about the selective collection, however with the implementation of actions and continuous use of bins, the results were satisfactory, since the students have learned that it is possible to preserve the environment with simple everyday by reducing , reuse, re-education and recycling.